Calcification of breast artery as detected by mammography: association with coronary and aortic calcification - SOYLU, Ayşegül İdil (Turk J Med Sci, 2019)
BACKGROUND/AIM: Coronary artery calcification (CAC) and aortic calcification (AC) are significant risk factors for coronary atherosclerosis. This study investigated how breast arterial calcification (BAC) detected from routine mammography correlates with coronary artery calcification and aortic calcification. MATERIALS AND METHODS: A total of 404 female patients above 40 years of age who, within a 6-month period, had undergone thoracic computed tomography and mammography for various reasons were screened retrospectively at our clinic. Mammographies were assessed for BAC and thoracic CT investigations were assessed for CAC and AC. Patients included in the study were scored as 0 (none), 1 (mild), 2 (moderate), or 3 (severe) depending on the number and shape of CAC, AC, and BAC lesions observed. RESULTS: Four hundred and four females were enrolled in the study. While BAC was detected in 123 patients, no BAC was observed in the other 281 patients. In the BAC-positive patients, the rates of CAC (45.5% vs. 19.9%, P < 0.001) and AC (67.5% vs. 32.4%, P < 0.001) were notably higher than in the BAC-negative patients. In addition, multivariate regression analysis detected the presence of BAC as an independent variable for both CAC and AC. CONCLUSION: The presence of BAC appeared to be a significant risk factor for CAC and AC, and the BAC grade was considered an independent risk factor for CAC.